Evaluation of Self-Care and Self-Efficacy in Patients Experiencing Phantom Pain After Amputation - KATRAN, HAMDİYE BANU (My University, 2024)
Objective: This study was conducted with a comparative and descriptive research design to evaluate the self-care agency and self-efficacy of patients who experienced phantom pain after limb amputation. Method: The population of the study consisted of 54 patients who underwent limb amputation operations in a university hospital in Istanbul between 1 January 2018 and 1 January 2020. Sample selection was not made, all patients included the population were reached by phone after their discharge. When the data were collected, one patient was excluded due to being younger than 18 years of age, 12 patients died, 9 patients had stump pain, and the study was completed with 32 patients. Data were collected using a “Personal Information Form”, the Visual Analog Scale, the Exercise of Self-Care Agency Scale and the Self-Efficacy Scale. Results: The mean Exercise of Self-Care Agency Scale score of the patients was found to be 79.37±21.55. Their mean total Self-Efficacy score was 70.00±16.10. There was no statistically significant relationship between postoperative phantom pain and scale scores. Conclusion: It was determined that patients who experienced phantom pain after amputation had moderate self-care agency and perceived self-efficacy levels. Keywords: Amputation, phantom limb pain, self-care, self-efficacy.
Keywords: Hemşirelik; Cerrahi Hastalıkları Hemşireliği; Sağlık Bilimleri; Nursing; Surgical Nursing; Health Sciences; Klinik Tıp (MED); Klinik Tıp; HEMŞİRELİK; Clinical Medicine (MED); CLINICAL MEDICINE; NURSING; Farmakoloji (hemşirelik); Onkoloji (hemşirelik); Asistan Hemşirelik; Tıbbi ve Cerrahi Hemşirelik; Annelik ve Ebelik; LPN ve LVN; Acil Tıp Hemşireliği; Yoğun Bakım Hemşireliği; İleri ve Uzman Hemşirelik; Hemşirelik (çeşitli); Genel Hemşirelik; Pharmacology (nursing); Oncology (nursing); Nurse Assisting; Medical and Surgical Nursing; Maternity and Midwifery; LPN and LVN; Emergency Nursing; Critical Care Nursing; Advanced and Specialized Nursing; Nursing (miscellaneous); General Nursing; Amputation; phantom limb pain; self-care; self-efficacy